Impact of short-term pausing of oral corticosteroids on blood eosinophil count in patients with severe asthma - Biener, Leonie; Milger, Katrin; Suhling, Hendrik; Korn, Stephanie; Pizarro, Carmen; Skowasch, Dirk (Pneumologie, 2022)
Background The peripheral blood eosinophil count (BEC) is a well-established and easily accessible biomarker for asthma patients and crucial for the therapeutic decision regarding monoclonal antibody (mAB) therapy. Oral corticosteroid therapy frequently hinders the correct evaluation of BEC in patients with severe asthma, but a discontinuation of such therapy frequently comes along with severe side effects. Therefore, we examined the effect of a short 24-hour pause of OCS treatment on BEC in patients with severe asthma and followed-up whether patients with a then increased eosinophil count benefited from mAB-therapy, as expected.Methods In this multicentre study we retrospectively included 24 patients with severe asthma and OCS therapy and determined their BEC count. Ten patients, where BEC count was obtained in the morning before taking medication (a de-facto 24-hour OCS pause), were assigned to group 1. Fourteen patients, where BEC was obtained after OCS tapering were assigned to group 2. Those who then received mAB treatment were followed up for treatment response (OCS dose, annual acute exacerbations, increase in forced expiratory volume in one second [FEV1] and asthma control test [ACT]) after ≥3 months.Results We included 24 patients with a median age of 60.5 [IQR: 17.3] years. Regarding all baseline characteristics except FEV1 (l), both groups did not differ significantly.Among all 24 patients, after pausing OCS therapy for 2 [5.5] days the BEC increased significantly from 125.0/μl [125] to 300/μl [232.5] (p<0.001). In both individual groups BEC increased significantly as well (150 [123] to 325 [305], p=0.005 and 70 [150] to 280 [255], p<0.001), with no significant difference for increase (BEC +170/µl [205.0] vs. +195 [222.5], p=0.886). Of all 24 patients, 13 (54.2%) reached eosinophil levels ≥300/µl, while 12 of them had not exceeded this threshold before.Subsequently, 20 patients (83.3%) received mAB-therapy with 55.5% demonstrating a good treatment response within 6 [1.5] months. The response rate in patients with BEC count ≥300/µl was even higher (75.0%). There was no difference in the treatment response rate between group 1 and 2 (p=0.092).Conclusion After just a short 24-hour pause of OCS therapy it was possible to demask a relevant eosinophilia in asthma patients, without risking severe side effects. In this manner, we enabled the possibility of achieving successful targeted mAB-therapy, according to the patient’s individual asthma phenotype.
Keywords: Asthma; Eosinophile; Antikörper; orale Kortikosteroide; schwergradiges Asthma